The Prevailing Catalytic Role of Meteorites in Formamide Prebiotic Processes - Raffaele Saladino; Lorenzo Botta; Ernesto Di Mauro (Life, 2018)
Meteorites are consensually considered to be involved in the origin of life on this Planet for several functions and at different levels: (i) as providers of impact energy during their passage through the atmosphere; (ii) as agents of geodynamics, intended both as starters of the Earth’s tectonics and as activators of local hydrothermal systems upon their fall; (iii) as sources of organic materials, at varying levels of limited complexity; and (iv) as catalysts. The consensus about the relevance of these functions differs. We focus on the catalytic activities of the various types of meteorites in reactions relevant for prebiotic chemistry. Formamide was selected as the chemical precursor and various sources of energy were analyzed. The results show that all the meteorites and all the different energy sources tested actively afford complex mixtures of biologically-relevant compounds, indicating the robustness of the formamide-based prebiotic chemistry involved. Although in some cases the yields of products are quite small, the diversity of the detected compounds of biochemical significance underlines the prebiotic importance of meteorite-catalyzed condensation of formamide.